Corporate celebration : play, purpose, and profit at work - Deal, Terrence E. (Berrett-Koehler Pub., 1998)
"How ceremonies can be used to build relationships, relieve tension, level the hierarchy, create excitement, transform losses into gains, and provide access to life's deeper lessons."--Cover.